The Tourist State : Performing Leisure, Liberalism, and Race in New Zealand - Werry, Margaret (Book collections on Project MUSE., 2011)
No longer the dreary sheep farm at the end of the world, the New Zealand of the new millennium is a hot global ticket, heralded for its bicultural dynamism, laid-back lifestyle, and scenery extraordinary enough to pass for Tolkien's Middle Earth. How this image was crafted is the story The Tourist State tells. In a series of narratives that address the embodied dimensions of biopolitics and explore the collision of race, performance, and the cultural poetics of the state, Margaret Werry exposes the real drama behind the new New Zealand, revealing how a nation was sold to the world-and to itsel.